Презумпция вины: роман / Анна Бабина - Бабина Анна (Имена. Российская проза, 2024)
Экземпляры: ЦБ/26/29 (20250403) / Инвентарный номер: 67878 / Цена: 594.00 / Сис.шифр: Р2 / Авт.знак: Б 12 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6